(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, we introduce and study the new class of sets, namely Regular Feebly Generalized Closed (briefly \(RFG\)-closed) sets, Regular Feebly Generalized neighborhoods (briefly \(RFG\)-nbhd), \(RFG\)-interior and \(RFG\)-closure in topological spaces and also some properties of new concepts have be en studied.